Biblical vs. Human Paradoxes, and Ways of Dealing with Post-Paradoxical Confusion - Jaffae/Kolomiytseva, O. A. (Cognition, Communication, Discourse, 2018)
This article proposes a comparative study of semantics and pragmatics of human and biblical paradoxes in English discourse. Paradoxes are part of the subconscious code of language. The author uses methods of cognitive linguistics, pragmatics, psycholinguistics, and discourse analysis to prove that manipulative human paradoxes are mentally destructive for the addressee, since they cause post-paradoxical confusion. And conversely, biblical paradoxes are beneficiary for the recipient, which makes them an effective tool in biblical paradoxical therapy.